The role and influence of "Champions" in a community-based lifestyle risk modification programme - Aoun, Samar; Shahid, Shaouli; Le, L.; Packer, Tanya (Sage Publications Ltd., 2012)
This article describes the training and implementation of the Waist Disposal Challenge in service clubs in Western Australia in 2009–2010. Ninety-three Champions from 52 clubs were trained to deliver educational presentations to 1100 peers and facilitate a BMI competition among 764 peers. Champions reported significant improvements in their knowledge and confidence to motivate their peers to make changes to their diet and physical activity with 82% of participants completing the BMI competition and on average 58% experiencing and sustaining a BMI reduction for 12 months. It is evident that the Champions had influenced the uptake and success of the intervention.